Mendeteksi Otentikasi File Audio Menerapkan Metode Ripemd-128 - Maria (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Audio file is a means of information from one person to another or from a group to another. The development of computerized technology has greatly increased. Audio files are very vulnerable to fraud, eavesdropping and data theft by irresponsible parties. In order to maintain the security of audio files, this can be done by using cryptographic techniques. Cryptography is a collection of techniques that are useful for securing information. In addition to securing information, it also maintains the confidentiality and integrity of the information. Cryptography is used for important communications such as communications among the military, diplomats, and spies. But nowadays cryptography is more non-repudiation.RIPEMD-128 is a cryptographic hash function designed for implementation on software with 32 bit architecture.